Strategi Pemberdayaan Anak Putus Sekolah Melalui Rumah Belajar dalam Mewujudkan Pendidikan Berkelanjutan di Desa Duria Kecamatan Lolofitu Moi Kabupaten Nias Barat - Sianturi, Juwilda; Batubara, Beby Masitho; Angelina, Nina (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
This study focuses on the high number of school dropouts in Duria Village, Lolofitu Moi District, West Nias Regency, which is influenced by various factors such as long school distances, limited transportation, low family income, and inadequate educational facilities. The purpose of this study is to identify the main causes of school dropout and develop empowerment strategies through learning homes to support continuing education. This study uses a qualitative method with an in-depth interview approach, participatory observation, and documentation to collect comprehensive data. The results of the study show that the learning home program is able to help children drop out of school by improving practical skills, material understanding, and developing their entrepreneurial spirit. Although several obstacles such as children's internal factors, family socio-economic conditions, and lack of environmental support are still obstacles, overall, learning homes have proven to be an effective strategy. This program not only plays a role in reducing the dropout rate in Duria Village, but also has great potential to be applied in other areas that face similar problems.